2017
DOI: 10.1113/ep086507
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid, external carotid and vertebral artery blood flow responses to 3 days of head‐out dry immersion

Abstract: What is the central question of this study? The extent to which weightlessness associated with a fluid shift from the peripheral to the central circulation influences the blood flow in each cerebral artery remains unknown. The present study was designed to explore the effect of short-term weightlessness conditions on both anterior and posterior cerebral blood flow. What is the main finding and its importance? Short-term weightlessness affects both anterior and posterior cerebral vasculature. However, a heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
5
10
0
Order By: Relevance
“…failed to observe any variation in CBF as measured by Doppler ultrasound. However, they did observe an increase in CVR [25]. Compared with the literature, our results showing a decrease in CBF after 5-day DI are consistent with the increase in CVR measured during the rst week in simulated microgravity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…failed to observe any variation in CBF as measured by Doppler ultrasound. However, they did observe an increase in CVR [25]. Compared with the literature, our results showing a decrease in CBF after 5-day DI are consistent with the increase in CVR measured during the rst week in simulated microgravity.…”
Section: Discussionsupporting
confidence: 92%
“…CPP is the result of mean arterial pressure (MAP) and ICP, according to the equation CPP = MAP -ICP [24]. Studies have shown that MAP does not seem to vary signi cantly in studies in HDBR [3] and after 3-day DI [25], consistent with our nding that blood pressure remained unchanged.…”
Section: Discussionsupporting
confidence: 89%
“…Other authors, however, reported an increase of middle cerebral vein velocity and jugular vein, portal vein and thyroid volume, but these findings were obtained only during the first 2 h of DI (Arbeille et al, 2017). Another recent study failed to reveal changes in blood flow in either cerebral artery, but internal carotid and vertebral arteries conductance decreased significantly on the 2nd and 3rd day of DI (Ogoh et al, 2017).…”
Section: Hemodynamic Changes In DImentioning
confidence: 93%
“…Indeed, a decrease in autoregulatory index Mxa associated with an increase in the cross-spectral phase shift were observed in 12 healthy male subjects. Ogoh et al (2017) showed in the same study that DI affected both anterior and posterior cerebral vasculature, but did not provoke a heterogeneous CBF response in each cerebral artery (internal carotid, external carotid, common carotid, and vertebral arteries) measured by Doppler ultrasonography. As previously suggested for spaceflight, one suggestion for CA improvement is that microgravity could increase the responsiveness of cerebral vascular smooth muscle to changes of transmural pressure (Iwasaki et al, 2007).…”
Section: Impacts Of Spaceflight Analogs On Cerebral Autoregulationmentioning
confidence: 79%